2020
DOI: 10.3390/ijms22010155
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of Brassinosteroid Analogues with a Nitrogen-Containing Side Chain

Abstract: Brassinosteroids are a class of plant hormones that regulate a broad range of physiological processes such as plant growth, development and immunity, including the suppression of biotic and abiotic stresses. In this paper, we report the synthesis of new brassinosteroid analogues with a nitrogen-containing side chain and their biological activity on Arabidopis thaliana. Based on molecular docking experiments, two groups of brassinosteroid analogues were prepared with short and long side chains in order to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…For example, brassinosteroids include brassinolide, castasterone, 24-epibrassinolide, and 28-homocastasterone. Synthetic analogues of BRs, the physiological activity of which is still being tested [ 22 ], are also available. Generally, the role of brassinosteroids in plants is important for regulating their growth and development, while BRs also have a protective effect in plants that are growing under stressful conditions such as drought [ 23 ], salinity [ 24 ], heavy metal stress [ 25 , 26 ], or low temperatures [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, brassinosteroids include brassinolide, castasterone, 24-epibrassinolide, and 28-homocastasterone. Synthetic analogues of BRs, the physiological activity of which is still being tested [ 22 ], are also available. Generally, the role of brassinosteroids in plants is important for regulating their growth and development, while BRs also have a protective effect in plants that are growing under stressful conditions such as drought [ 23 ], salinity [ 24 ], heavy metal stress [ 25 , 26 ], or low temperatures [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main difficulties found in the synthesis of BRs is the replication of the side alkyl chain due to the presence of at least three chiral centers. Thus, in the quest for new active analogs, various BRs analogs have been obtained by incorporating important structural modifications in their side chain [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly used in research on multitarget and multiaction traditional Chinese medicine. Molecular docking allows a receptor–ligand complex to be docked according to an analysis of the specific receptor docking sites and the drug molecule [ 20 ]. Although studies have shown that luteoloside has anti-tumor effects, the specific targets are still unclear, and neuroblastoma has not yet been studied to determine the effects and mechanisms of luteoloside.…”
Section: Introductionmentioning
confidence: 99%